Adapting a Behavioral Intervention for Alcohol Use and HIV Medication Adherence for Lay Counselor Delivery in Cape Town, South Africa: A Case Series. Issue 2 (May 2022) - Belus, Jennifer M.; Rose, Alexandra L.; Andersen, Lena S.; Ciya, Nonceba; Joska, John A.; Myers, Bronwyn; Safren, Steven A.; Magidson, Jessica F.
Highlights: A CBT intervention for problematic alcohol use can be adapted for lay providers. Low motivation to change and substance-using social networks are patient challenges. Lay provider acceptance of low patient readiness to change requires supervision. Addressing multiple comorbidities is challenging due to session time constraints. Abstract: Human immunodeficiency virus (HIV) and problematic alcohol use are two ongoing and interconnected epidemics in South Africa, with untreated problematic alcohol use associated with poorer HIV treatment outcomes and disease progression. A lack of trained mental health providers is a primary barrier to increasing access to evidence-based treatment in this setting. To address this gap, we integrated evidence-based intervention components for problematic alcohol use and antiretroviral therapy (ART) adherence, adapted for lay provider delivery in an HIV primary care setting in Cape Town, South Africa. The intervention, locally termed "Khanya" in isiXhosa, which means glow, direction, or light, comprises Life Steps adherence counseling, motivational interviewing, behavioral activation, and relapse prevention, including mindfulness-based relapse prevention components. In this case series, we present a detailed description of the intervention and provide three clinical cases of individuals who received the Khanya intervention to showcase necessary clinical adaptations and the supervision needed for optimal treatment delivery, flexibility in intervention delivery, and overall successes and challenges. We present descriptive data on alcohol use and ART adherence outcomes for the cases to supplement the narrative discussion. Successes of intervention delivery included participant uptake of mindfulness skills, reductions in alcohol use despite varying levels of motivation, and interventionist mastery over various clinical skills. Challenges included delivering the intervention within the allotted time and the strong influence of substance-using social networks. Overall, a pragmatic approach to intervention delivery was necessary, as was ongoing support for the interventionist to promote fidelity to both treatment components and therapeutic skills. Trial registration: ClinicalTrials.gov identifier: NCT03529409. Trial registered on May 18, 2018.